Circulating TNF receptors predict cardiovascular disease in patients with chronic kidney disease. Issue 19 (May 2017) - Bae, Eunjin; Cha, Ran-Hui; Kim, Yong C.; An, Jung N.; Kim, Dong K.; Yoo, Kyung D.; Lee, Su M.; Kim, Myoung-Hee; Park, Jung T.; Kang, Shin-Wook; Park, Jae Y.; Lim, Chun S.; et al.
Abstract : Abstract: Cardiovascular disease (CVD) is the main public health problem in patients with chronic kidney disease (CKD); however, there is no established biomarker for predicting CVD morbidity and mortality in CKD. The aim of this study was to evaluate the role of circulating tumor necrosis factor receptors (cTNFRs) in predicting CVD risk in CKD patients. We prospectively recruited 984 patients with CKD from 11 centers between 2006 and 2012. The levels of cTNFR1 and cTNFR2 were determined by performing an enzyme-linked immunosorbent assay. During the mean follow-up period of 4 years, 36 patients experienced a CVD event. The median serum concentrations of cTNFR1 and cTNFR2 were 2703.4 (225.6–13, 057.7) and 5661.0 (634.9–30, 599.6) pg/mL, respectively, and the cTNFR1 level was closely correlated with the cTNFR2 level ( r = 0.86, P < .0001). The urinary protein-to-creatinine ratio (UPCR) and estimated glomerular filtration rate (eGFR) were significantly correlated with the cTNFR2 level ( r = 0.21 for UPCR, r = −0.67 for eGFR; P < .001 for all). Similar correlations were observed for serum cTNFR1 ( r = 0.21 for UPCR, r = −0.75 for eGFR; P < .001 for all). In the Cox proportional hazard analyses, cTNFR1 (hazard ratio [HR] 2.506, 95% confidence interval [CI] 1.186–5.295, P = .016) and cTNFR2 (HR 4.156, 95% CI 1.913–9.030, P < .001) predicted CVD risk even after adjustment for clinical covariates, such as UPCR, eGFR, and high-sensitivity C-reactive protein. cTNFR1 and 2 are associated with CVD and other risk factors in CKD, independently of eGFR and UPCR. Furthermore, cTNFRs could be relevant predictors of CVD in CKD patients. Abstract : Supplemental Digital Content is available in the text